The feminist political economy of Covid-19: Capitalism, women, and work. - Cohen, Jennifer; van der Meulen Rodgers, Yana (Global public health, 2021)
Analysing the pandemic through a feminist political economy lens makes clear how gender, race, and class structures are crucial to the functioning of capitalism and to understanding the impacts of the pandemic. The way capital organises production and reproduction combines with structures of oppression, generating vulnerability among the racialised and gendered populations worst impacted by Covid-19. Using global data, this commentary shows that during the pandemic, women experienced relatively greater employment losses, were more likely to work in essential jobs, and experienced a greater reduction in income. Women were also doing more reproductive labour than men and were more likely to drop out of the labour force because of it. Analyses of capitalism in feminist political economy illustrate how capital accumulation depends on women's oppression in multiple, fundamental ways having to do with their paid and unpaid work. Women's work, and by extension their health, is the foundation upon which both production and social reproduction rely. Recognising the pandemic as endogenous to capitalism heightens the contradiction between a world shaped by the profit motive and the domestic and global requirements of public health.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; capitalisme; covid-19; histoire et politique; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; violences

Women of the great barrier reef: Stories of gender and conservation - Foxwell-Norton, Kerrie; Anderson, Deb; Leitch, Anne M. (Queensland Review, 2021)
In the late 1970s, Carden Wallace was at the beginning of her lifelong exploration of the Great Barrier Reef - and indeed, reefs all over the world. For Wallace, who is now Emeritus Principal Scientist at Queensland Museum, the beginning of her Reef career coincided with the emergence of both feminist and environmental movements that meant her personal and professional lives would be entwined with a changing social, cultural and political milieu. In this article, we couple the story of Wallace's personal life and her arrival in coral science to identify the Reef as a gendered space ripe to explore both feminist and conservation politics. The article is part of a broader Women of the Reef project that supports a history of women's contribution to the care and conservation of the Reef since the 1960s. In amplifying the role of women in the story of the Reef, we find hope in the richness of detail offered by oral history to illuminate the ways discourse on the Reef and its women sits at the intersection of biography, culture, politics and place. In these stories, we recognise women's participation and leadership as critical to past challenges, and to current and future climate change action. By retelling modern Reef history through the experiences and achievements of women, we can develop new understandings of the Reef that disrupt the existing dominance of patriarchal and Western systems of knowledge and power that have led us to the brink of ecological collapse. © The Author(s), 2022.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; approches et analyses; australie; changements climatiques; environnement; histoire et politique; océanie; patriarcat; projet charge mentale; périodes historiques; régions géographiques; rôle des femmes dans la protection de la grande barrière de corail; systèmes d'oppressions; thématiques

La puissance féministe - Gago, Verónica (Éditions de la rue Dorion, 2021)
L’Amérique du Sud est un des coeurs battants du féminisme contemporain. Des millions de femmes y prennent la rue contre les féminicides, les violences qui frappent les minorités de race et de genre, les lois qui répriment l’avortement et le développement néo-extractiviste. Figure majeure du féminisme latino-américain, Verónica Gago réinscrit ces bouleversements dans l’émergence d’une internationale féministe et propose, avec La puissance féministe, un antidote à tous les discours de culpabilité et de victimisation. En se réappropriant l’arme classique de la grève, en construisant un féminisme populaire, radical et inclusif, les mouvements sud-américains ont initié une véritable révolution. C’est à partir de l’expérience de ces luttes que Gago reconceptualise la question du travail domestique et de la reproduction sociale, expose les limites du populisme de gauche et dialogue avec Spinoza, Marx, Luxemburg ou Federici. Parce qu’il unit la verve politique du manifeste aux ambitions conceptuelles de la théorie, La puissance féministe est un livre majeur pour saisir la portée internationale du féminisme aujourd’hui.
Keywords: 2000 à aujourd'hui; amérique latine; amériques; approches et analyses; care; cours; cycles supérieurs; fem7000; histoire et politique; justice sociale; militance; patriarcat; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; violences

How far the ecowarrior will go: An ecofeminist reading of disney's Moana - Hernawati, Mala (3L: Language, Linguistics, Literature, 2021)
This article attempts to look into the fictional narrativization of women's significant and distinctive relationship with nature in Disney's Moana. Emphasizing the power and the unity of women and nature in Polynesian indigenous culture, Moana suggests that the destruction of nature results from exploitative and manipulative masculinity. Through ecofeminist perspectives, this essay observes that Moana offers critical views and promotes awareness of gender and environmental issues. These ideas are communicated through the visual and verbal depiction of power relations that defy patriarchal tradition alongside the expressions of protest against devaluation and abuse of nature and women. To put it in the context of the development of themes in Disney's princess line, Moana's presence can be a novel alternative to the typical images of women, namely a new portrayal of a female character whose primary concern is not romance but instead the sustainability of the environment where she lives. This study also confirms that Disney's animated princess films continuously adjust with the dynamics of global feminist discourse. © 2021 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; capitalisme; environnement; film d'animation; féminisme pop; histoire et politique; patriarcat; princesse disney; projet charge mentale; périodes historiques; systèmes d'oppressions; thématiques; écoféminisme

Examining the cracks in universal water coverage: Women document the burdens of household water insecurity - Radonic, Lucero; Jacob, Cara E. (Water Alternatives, 2021)
L’accès universel à l’eau potable est considéré comme une caractéristique déterminante des villes du Nord global. Cet article décrit les défis quotidiens auxquels sont confrontées les femmes de la classe ouvrière de Flint, dans le Michigan, lorsque la promesse d’une infrastructure d’eau moderne se fissure. En 2014, afin de réduire les coûts, la source d’eau potable de Flint a été transférée du lac Huron à la rivière Flint. Ce changement, et plus particulièrement la manière dont il a été géré, a entraîné une contamination de l’approvisionnement en eau par du plomb et des agents pathogènes. Si l’expérience de Flint est désormais un cas emblématique d’insécurité hydrique dans le Nord global, elle n’est pas unique. À travers une étude de cas élaborée dans le cadre d’un projet de recherche participative communautaire, cet article détaille comment l’insécurité hydrique a transféré la charge de l’approvisionnement en eau potable aux ménages individuels, et plus particulièrement aux femmes. Plutôt que de pouvoir compter sur la main-d’œuvre et l’expertise technique qui ont rendu l’eau potable dans la ville moderne, les habitants de Flint ont été soudainement rendus responsables de la sécurité de leur propre approvisionnement en eau. Nous expliquons comment la crise de l’eau de Flint a fait naître une « nouvelle normalité » ; Nous examinons les façons dont cette situation a donné naissance à un nouveau rapport à l'eau potable, caractérisé par un (re)retour à l'eau en bouteille ou filtrée (de l'eau du robinet) et par un changement dans la répartition des tâches nécessaires à la production d'eau potable. Les témoignages de femmes que nous présentons ici illustrent comment, lorsque l'eau uniforme moderne fait défaut, les gens commencent à voir des eaux hétérogènes.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; accès à l'eau potable; amériques; anthropologie; approches et analyses; capitalisme; discipline; eau en bouteille; environnement; histoire et politique; inégalités hommes-femmes; patriarcat; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Dead white men vs. Greta Thunberg: Nationalism, misogyny, and climate change denial in swedish far-right digital eedia - Vowles, Kjell; Hultman, Martin (Australian Feminist Studies, 2021)
In the autumn of 2018 Greta Thunberg started her school strike. Soon she and the Fridays For Future-movement rose to world-fame, stirring a backlash laying bare the intrinsic climate change denial of Swedish far-right digital media. These outlets had previously been almost silent on climate change, but in 2019, four of the ten most read articles on the site Samhällsnytt were about Thunberg, all of them discrediting the movement and spreading doubt about climate science. Using the conceptualisation of industrial/breadwinner masculinities as developed by Hultman and Pulé [2018. Ecological Masculinities: Theoretical Foundations and Practical Guidance. Routledge Studies in Gender and Environments. New York: Routledge], this article analyses what provoked this reaction. It explores how the hostility to Thunberg was constructed in far-right media discourse in the years 2018–2019, when she became a threat to an imagined industrial, homogenic and patriarchal community. Using conspiracy theories and historical tropes of irrational femininity, the far right was trying to protect the usually hidden environmental privileges, related to unequal carbon emissions and resource use, that Thunberg and her movement made visible. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discous dominant; environnement; europe; extrême-droite; histoire et politique; misogynie; médias; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; suède; systèmes d'oppressions; thématiques; violences